Research on the treatment of oil-polluted wastewater with olive oil production waste - Abdullayeva Maya; Mammadova Zuleykha (BIO Web of Conferences)
Despite the development and use of waste-free technological processes in the oil refining industry, the modernization of oil production enterprises, the improvement of the processes of storage and transportation of oil products, the pollution of water bodies and lands with oil products is quite high. The scientific significance of the work lies in the justification of the possibility of obtaining oil-absorbing sorbents from olive peel and the determination of the dependence of the specific capacity of the sorbent on the initial oil content in water and the amount of the sorbent. The olive groves of “Absheron Olive Garden” LLC are the result of the successful implementation of the concept of the development of the non-oil sector and agriculture in our country, and they are used in the treatment of waste water. The practical importance of the work lies in the development of the production method of oil absorbent sorbents and the development of proposals for the creation of territorial ecological-technological complexes.